THE EFFECT OF EL NINO AND LA NINA ON THE INTENSITY OF DETERMINING QIBLA DIRECTION - Muhammad Himmatur Riza; Nihayatul Minani (Al-Hilal: Journal of Islamic Astronomy, 2021)
On the basis of the annual pseudo motion of the Sun, there is a division of the seasons. In terms of seasons, there are several natural phenomena that can affect the seasons on earth, especially the natural phenomena of El Nino and La Nina. In Indonesia, El Nino can result in a longer dry season and La Nina can cause a longer rainy season. Thus, any research related to the influence of El Nino and La Nina is very important to do to determine whether these two natural phenomena affect the intensity of determining the direction of the Qibla. This research is included in the Library Research using qualitative research methods with a descriptive format. Data collection techniques used are documentation or literature and non-participant observation. Meanwhile, to analyze the data, the authors processed the field data obtained from the Class I Semarang Climatology Office to obtain the average climatological elements during the year of El Nino and La Nina, then the results were implemented in determining the direction of the Qibla. This study resulted in the finding that La Nina was sufficient to influence the implementation of determining the direction of the Qibla because at the time of La Nina the rain continued to occur throughout the year.